EVALUASI PELAKSANAAN FORUM KESEHATAN DESA DALAM MENDUKUNG PELAKSANAAN PENGEMBANGAN DESA SIAGA AKTIF DI DESA GULON KABUPATEN MAGELANG - Sapri Fidora; Priyadi Nugraha Prabamukti; Besar Tirto Husodo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
“Desa Siaga Aktif” is a village where people easy to get access to health services and have effort in addressing health problems based on community resources. Gulon Village is currently stratified Desa Siaga Aktif Pratama. One of DesaSiagaAktif components is activeness in village health forum (FKD).The research aims to evaluate the implementation of FKD in Gulon village at the input stage (man, material, method and money), process stage (planning, organizing, implementation, supervision) and output stage (effectiveness and efficiency of the program).Design research is qualitative with descriptive approach method. Research subject uses 6 main informants and 2 informant triangulation. Qualitative data analysis uses thematic analysis.Test validation uses source triangulation. At the input stage, FKD boardnumber and level of education, infrastructure and problem solving method is enough to manage FKD, while funding is not availableyet. Management capability needs to improvement.At the process stage, planning and supervision of FKD does not available yet due to absence of regular meetings for FKD planning activities. FKD organizing has been established, but the implementation of activities adhere regular activities in Gulon Village. At the output stage, effectiveness and efficiency of FKD need improvement because of target achievement not available yet.FKD Implementation in Gulon Village has not enough to support “DesaSiagaAktif” development program in Magelang District due to lack of required resources and management of FKD